THE ROLE OF SONGS IN ENHANCING LANGUAGE SKILLS AND MOTIVATION FOR YOUNG LEARNERS (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2024)
Throughout history, music has been intertwined with the educational journey of children. However, it is worth noting that songs stand out as an especially potent tool for instructing languages to young learners. This article delves into how songs enhance not only vocabulary and listening skills but also render language classes more engaging and enjoyable.By employing songs as a means of instruction, educators can establish a calm and authentic setting that inspires students while also improving their memory and pronunciation abilities.This approach also enables young learners to feel included in a group, promoting improved interaction and reducing the intimidation associated with language learning.